DEVELOPMENT OF CREATIVE ABILITY IN STUDENTS ON THE BASIS OF A COMPETENT APPROACH - Gadaymoratov Shuhrat Mamayusupovich; Eshpolatova Jang‘il Eshankulovna (Bright Mind Publishing, 2025)
This article presents opinions on improving creativity among primary school students. In it, the role and importance of motivation of creative abilities in elementary school students to acquire the necessary knowledge, skills, qualifications and competencies and to be able to apply them to life, as well as to determine the creative thinking abilities of elementary school students and specific aspects of the development of creative thinking motivations are described.
Keywords: Student, education, thinking, creativity, skill, skill competence, thinking, creativity, ability, freedom.